Biotechnology Teacher Training - Bielec, Barbara (Proceedings of the Wisconsin Space Conference, 2011)
An integral part of enhancing science education is training teachers in current content and techniques, and biotechnology is one of the technologies that will be needed to maintain living systems in space. The BioPharmaceutical Technology Center Institute (BTC Institute) offered two graduate education courses in biotechnology for teachers during summer 2011. Each weeklong course was held at the BioPharmaceutical Technology Center. Biotechnology: The Basics and Biotechnology: Beyond the Basics were designed and presented to provide teachers with training, background and curriculum materials (including information about NASA and biotechnology), so that they may implement hands-on biotechnology in their classrooms. Teachers of a wide variety of subjects with varied levels of experience were active participants in lab-based training.Â 